Structural similarities in the CPC clip motif explain peptide-binding promiscuity between glycosaminoglycans and lipopolysaccharides. Issue 136 (30th November 2017) - Pulido, David; Rebollido-Rios, Rocío; Valle, Javier; Andreu, David; Boix, Ester; Torrent, Marc
Abstract : Lipopolysaccharides (LPSs) and glycosaminoglycans (GAGs) are polymeric structures containing negatively charged disaccharide units that bind to specialized proteins and peptides in the human body and control fundamental processes such as inflammation and coagulation. Surprisingly, some proteins can bind both LPSs and GAGs with high affinity, suggesting that a cross-communication between these two pathways can occur. Here, we explore whether GAGs and LPSs can share common binding sites in proteins and what are the structural determinants of this binding. We found that the LPS-binding peptide YI12WF, derived from protein FhuA, can bind both heparin and E. coli LPS with high affinity. Most interestingly, mutations decreasing heparin binding in the peptide also reduce LPS affinity. We show that such mutations involve the CPC clip motif in the peptide, a small three-dimensional signature required for heparin binding. Overall, we conclude that negatively charged polysaccharide-containing polymers such as GAGs and LPSs can compete for similar binding sites in proteins, and that the CPC clip motif is essential to bind both ligands. Our results provide a structural framework to explain why these polymers can cross-interact with the same proteins and peptides and thus contribute to the regulation of apparently unrelated processes in the body.